2016
DOI: 10.1007/s40257-016-0183-7
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Nervous System in the Pathophysiology of Psoriasis: A Review of Cases of Psoriasis Remission or Improvement Following Denervation Injury

Abstract: As most efforts in the last decade have focused on the immunologic basis of inflammatory skin disease, there has been less emphasis on the role of the nervous system in the disease process of psoriasis. Evidence in support of the neurocutaneous pathway has come from observations of patients experiencing unilateral improvement and even complete remission following nerve damage in the affected dermatomal region. The aim of this review was to investigate the role of neuropeptides in the intricate pathophysiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 34 publications
2
44
0
Order By: Relevance
“…To date, several case reports have described psoriatic lesions with acquired central or peripheral nerve damage that exhibited unilateral local clearance or improvement (2). Consistent with those clinical reports, another study using a murine model of psoriasis demonstrated that loss of cutaneous innervation via traumatic nerve injury resulted in reduction of the clinical symptoms of psoriasis (3).…”
Section: Discussionmentioning
confidence: 64%
“…To date, several case reports have described psoriatic lesions with acquired central or peripheral nerve damage that exhibited unilateral local clearance or improvement (2). Consistent with those clinical reports, another study using a murine model of psoriasis demonstrated that loss of cutaneous innervation via traumatic nerve injury resulted in reduction of the clinical symptoms of psoriasis (3).…”
Section: Discussionmentioning
confidence: 64%
“…Identifying these mechanisms could shake up the established dogma regarding sensory perception as well as contribute to a better understanding of skin diseases with psychic participation, such as psoriasis. The existence of psoriasis remission or improvement following denervation injury could support this hypothesis …”
Section: Discussion and Perspectivesmentioning
confidence: 87%
“…Upon secretion from nerve endings, NGF can bind to keratinocytes’ NGF receptors, thus promoting keratinocytes’ de‐differentiation and hyperproliferation . Furthermore, these mediators promote vasodilatation and innate and adaptive local neurocutaneous inflammation, which contribute to psoriasis pathogenesis . Additionally, higher concentrations of NGF, SP and CGRP are found in psoriasis lesions than in healthy skin …”
Section: Discussionmentioning
confidence: 99%